O comum e o singular no pensamento de Hannah Arendt - Rocha, Antonio Glauton Varela (2020)
The present research has as its main objective evaluating between the concepts of common and singular as parts of the thought of Hannah Arendt. The hypothesis I seek to support and that shows itself as the main point of this thesis is the thinking of Hannah Arendt is deeply marked as balance between common and singular. The schedule in building up the argumentation begins by the description of individual and historic experiences which point out to an unbalance the between common and singular. It then follows by the explicit of experiences that point out to the aforementioned balance. Lastly, the discussion closes with the exhibition of thinking and judging categories as a foundation for an ethical meditation that aims for an accountability to the common world. We indicate the concept of solitude, on the first moment, as the experience that leads the unbalance between common and singular to its extreme. This specificity will be developed by pointing out ways that lead to solitude, firstly in the Arendtian critique of romantic introspection, then in the process of massification and, last of all, in totalitarianism, especially on concentration camps. In the second moment, we characterize the common world as the category that best expresses the equilibrium between the common and the singularity. On it, the reflection about the common world will fit as a basis to indicate the foundations of individualism in Arendt. For the last argumentative step on the thesis, we seek to show the equilibrium between the common and the singular also from actions of life and the Spirit, especially regarding the ones of thinking and judging. At this point we highlight how thought and judgement in Arendt cannot be considered without a bond to the world. Ultimately, we aim at how judgement implies in an ethical necessity before the political impact in the world, occasioned by the lack of thought and judgement. The thesis then closes pointing to the responsibility of preservation of the common world, being it the space in which the balance between common and singular is best validated, and also where we attain more power of resisting to solitude.